KEPATUHAN WAJIB PAJAK UMKM : PERAN SOSIALISASI PERPAJAKAN, KEPERCAYAAN KEPADA PEMERINTAH, DAN KESADARAN WAJIB PAJAK DI DESA SRIHARJO BANTUL - Nabiilah Junga, Jihaan; Airawaty, Diana (JURNAL ILMIAH EDUNOMIKA, 2025)
This study was conducted to determine and analyze the compliance of MSME taxpayers with the role of tax socialization, trust in the government, and taxpayer awareness in Sriharjo Village, Bantul. The population of this study was all taxpayers who have MSME businesses located in Sriharjo Village, Bantul Regency, Special Region of Yogyakarta. The data analysis technique used SPSS. The results of the study showed that tax socialization had no significant effect on MSME taxpayer compliance in Sriharjo Village. Trust in the government had no significant effect on MSME taxpayer compliance. Taxpayer awareness had a positive and significant effect on MSME taxpayer compliance. Overall, the three independent variables, namely tax socialization, trust in the government, and taxpayer awareness, were proven to have a simultaneous effect on MSME taxpayer compliance in Sriharjo Village. This emphasizes the importance of synergy between government efforts and individual awareness in creating an effective tax system.